On a second-order differential problem with fractional derivatives of order greater than one - Tatar, Nasser-eddine (Mathematical Modelling and Analysis, 2013)
A second-order abstract problem with derivatives of non-integer order is investigated. The nonlinearity involves fractional derivatives between 1 and 2. Existence and uniqueness of mild and classical solutions are established in appropriate spaces. This work extends similar works with or without a derivative of first order and also a work of the present author, where the order of the derivatives were between 0 and 1.